Evaluation of Anticonvulsant Properties of Methanol Aerial Extract of Bryophyllum Pinnatum (Lam.) Oken (Crassulaceae) In Mice and Chicks (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Bryophyllum pinnatum is an environmental weed from the Crassulaceae family that is often used to treat convulsion, hypertension, diarrhea, insect bites, asthma and other ailments.Objectives: To evaluate the anticonvulsant potential of methanol aerial extract of Bryophyllum pinnatum plant in mice and chicks.Materials and Methods: The anticonvulsant potential was studied using Maximal electroshock Test (MEST) and pentylenetetrazol (PTZ) test in one day old chicks and mice at 250, 500 and 1000 mg/kg body weight of the extract i.p respectively. Positive control drugs used were sodium valproate (200 mg/kg) and phenytoin (20 mg/kg) in PTZ and MEST respectively while distilled water (10 ml/kg) i.p was used as negative control in all experiments.Results: The intraperitoneal LD50 of the extract was found to be greater than 5000 mg/kg body weight with an indication that the extract is relatively safe. Significant (p ≤ 0.05) prolongation of the mean onset of seizures was recorded with the extract at 1000 mg/kg body weight compared with normal saline treated group in PTZ induced seizures. Bryopyllum  pinnatum methanol aerial extract also significantly reduced the mean recovery time of seizures at doses 500 and 1000 mg/kg induced by MEST when compared with normal saline treated group. Conversely, a significant (p ≤ 0.05) delay in the mean onset of seizures was recorded with standard drugs, sodium valproate (200 mg/kg) and phenytoin (20 mg/kg) in PTZ and MEST respectively.Conclusion: Methanol extract of the aerial part of Bryophyllum pinnatum possesses anticonvulsant activities.